Guest Modulated Spin States of Metal Complex Assemblies. Issue 39 (30th August 2020) - Nakaya, Manabu; Ohtani, Ryo; Hayami, Shinya
Abstract : Recently, "host–guest chemistry" aspects of material science have received much attention, particularly in relation to moderating the functions of materials. In particular, magnetic properties involving the "magnetic ordering" and "spin crossover" of host–guest metal complex systems have been actively investigated in terms of their host–guest chemistry. That is, systems in which the magnetic properties are sensitive to perturbation by the uptake of guests (which thus act as chemical stimuli). Such guests (solvents, gases and organic molecules) very often influence the structures of both discrete metallosupramolecular assemblies as well as those of coordination polymers/metal‐organic frameworks (CPs/MOFs), providing a means for fine‐tuning their magnetic behavior, including the switching of their spin states. In this minireview, we report recent progress in the development and investigation of magnetic materials of both the CP and MOF categories as well as of discrete complexes whose properties are modulated by guests. Abstract : In this minireview, we discuss magnetic materials, characterized as being both "porous magnets" and "SCO complexes" in which the magnetic properties can be modulated by the presence or absence of guests residing in a metal complex's molecular framework. That is, the effect of guest molecules on both the structures and magnetic properties of the metal complex assemblies are discussed.